United States - Japan: the militant dilemma of an ancient empire (2017)
Relations between the United States and Japan have been close since the end of World War II. Both nations signed a Mutual Cooperation and Security Treaty that guaranteed Japan the defense of its nation without incurring a national armament to avoid the warlike behaviors previously presented by the Asian empire. Today the treaty is still underway, and although cooperation between them is in doubt, it seems that it remains firm and with the support of Asian countries that fear Chinese control in the area. Japanese support for the United States in the tensions of the Korean peninsula demonstrates the validity of the deal today, and Japanese government initiatives for the empowerment of the island can be interpreted as an evolution to this cooperation.